Srovnání zahraniční politiky Kanady a Ruska - případ Arktidy - Jánská, Lucie (Univerzita Karlova, Fakulta sociálních věd, 2014)
The study examines the foreign policy of the two major Arctic states, Russia and Canada. The main goal is to define what factors affect the formation of foreign policies of both countries and the way how applying Arctic foreign policies of Russia and Canada affects their relations in the region. First part of the study defines the Arctic region from geographical and legal terms, and briefly describes its history and also deals with Arctic actors (except Russia and Canada) and defines their objectives in the Arctic and finally the author also focuses on the Arctic Council as the most important institution for dealing with Arctic issues. The main part of the study deals with analysis of the Canadian and Russian Arctic strategy and examines the impact of internal and external factors on the formation of Arctic foreign policies of these countries. The category of external factors includes anarchy and power from the perspective of realism, interdependence from the perspective of liberalism and international norms and legitimacy from the perspective of constructivism; internal factors includes the public, societal groups, government organization and leaders. Author analyzes the formation of Russian and Canadian foreign policy using these factors and concludes, that dominant external factor in case of the. Práce se zabývá zkoumáním zahraniční politiky dvou nejvýznamnějších arktických států, Ruska a Kanady. Cílem práce je ověřit, jaké faktory ovlivňují její tvorbu, a jak způsob uplatňování arktické zahraniční politiky Ruska a Kanady ovlivňuje jejich vzájemné vztahy. V úvodní části autorka vymezuje arktický region z geografického i právního hlediska a stručně popisuje jeho historii, dále se zabývá jednotlivými arktickými aktéry (mimo Ruska a Kanady) a definuje jejich cíle v oblasti a prostor věnuje také Arktické radě coby nejdůležitějšímu orgánu pro řešení arktické problematiky. Stěžejní část práce se věnuje rozboru kanadské a ruské arktické strategie a zkoumání vlivu vnitřních a vnějších faktorů na tvorbu arktické ...